Effects of the inductively coupled Ar plasma etching on the performance of (111) face CdZnTe detector. (April 2020) - Song, Bing; Zhang, Jijun; Liang, Xiaoyan; Zhao, Shuhao; Min, Jiahua; Shi, Haozhi; Lai, Jianming; Wang, Linjun
Abstract: The effect of inductively coupled Ar plasma etching (ICP-Ar) instead of traditional Br–MeOH etching on the performance of CdZnTe detectors was studied. The optimal ICP etching parameters were determined by experiments. The XPS results indicated that the surface composition of CdZnTe etched by ICP-Ar had no obvious TeOx peak and was closer to stoichiometric ratio than that etched by Br–MeOH. The leakage current of ICP-Ar etched CdZnTe surface was significantly reduced, and the detection performance with the energy resolution was improved by 12%, as compared to Br–MeOH etched sample. Moreover, ICP-Ar etching abandoned the drawbacks of Br–MeOH by producing corrosive gases, making it safer and more environmentally friendly. Therefore, inductively coupled Ar plasma etching is expected to replace Br–MeOH etching and become an effective method for CdZnTe surface treatment.